Magnetic Resonance Imaging: Time‐Dependent T1–T2 Switchable Magnetic Resonance Imaging Realized by c(RGDyK) Modified Ultrasmall Fe3O4 Nanoprobes (Adv. Funct. Mater. 32/2018). (6th August 2018) - Bai, Chen; Jia, Zhengyang; Song, Lina; Zhang, Wei; Chen, Yi; Zang, Fengchao; Ma, Ming; Gu, Ning; Zhang, Yu
Abstract : Ning Gu, Yu Zhang, and co‐workers demonstrate in article number1802281 that time‐dependent T1 –T2 magnetic resonance imaging (MRI) of tumors can be achieved by gradual accumulation of c(RGDyK) modified ultrasmall Fe3 O4 nanoprobes. These nanoprobes are completely different from the others by exhibiting T1 ‐ and T2 ‐weighted enhancements at the same time, thus having potential to improve the diagnostic accuracy and sensitivity in MRI.